1996
DOI: 10.1007/bf01695660
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of 288 episodes of bacteremia in neutropenic cancer patients in a single institution

Abstract: Trends in causative organisms and sources of infection were studied in a series of 288 episodes of bacteremia in neutropenic cancer patients observed in a single institution from 1986 to 1993. The incidence of bacteremia increased significantly from 20 episodes per 1000 admissions in 1986 to 50 episodes per 1000 admissions in 1993 (p = 0.00001). Over the study period, a continuous increment in gram-positive bacteremia, which reached 81% of episodes in 1993 (p = 0.000001), was observed. Conversely, the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 25 publications
10
64
1
Order By: Relevance
“…Staphylococci and S. viridans were the most commonly isolated bacteria in this study (21). Moreover, in a multicentre study on febrile neutropenic patients in the USA Wisplinghoff et al (19) reported the outweigh of Gram-positive microorganisms as a cause of 62% and 76% of blood stream infections in 1995 and 2000 respectively, while only 22% and 14% of all blood stream infections originated from Gram-negative ones at the same time (19).…”
Section: Discussionmentioning
confidence: 47%
“…Staphylococci and S. viridans were the most commonly isolated bacteria in this study (21). Moreover, in a multicentre study on febrile neutropenic patients in the USA Wisplinghoff et al (19) reported the outweigh of Gram-positive microorganisms as a cause of 62% and 76% of blood stream infections in 1995 and 2000 respectively, while only 22% and 14% of all blood stream infections originated from Gram-negative ones at the same time (19).…”
Section: Discussionmentioning
confidence: 47%
“…A major aim of our study was to examine the ability of routine surveillance cultures to predict the causative agents of bacteremia, one of the most Table 2 Bacteremias and fungemias according to timing of hospitalization and delay after transplantation Streptococci 15 68 7 32 17 65 9 35 Coag-neg staphylococci 40 61 26 39 47 45 58 55 Other Gram-pos 8 57 6 43 6 32 13 68 Anaerobes 2 67 1 33 6 100 0 0 Gram-neg 25 52 23 48 36 44 45 56 Fungi 5 63 3 37 5 83 1 17 Total 95 59 66 41 117 48 126 52 frequent life-threatening infections in neutropenic patients. 9 Indeed, the mortality primarily or secondarily due to infections has been reported to reach 60% in some series of patients undergoing HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] That shift was probably caused by widespread administration of FQs prophylaxis, the almost universal use of CVCs and by chemotherapy regimens associated with severe mucositis. 31 In fact, in 2000 GP bacteria accounted for 76% of all BSIs in cancer patients in the United States. 29 However, this tendency has reversed again, with GN bacteria becoming more frequent than GP in many centers.…”
Section: Increase In Gram-negativesmentioning
confidence: 99%